Growth, distribution, and sectoral heterogeneity: Reading the Kaleckians in Latin America - Fernando Rugitsky (EconomiA, 2016)
The aim of this paper is to explore a parallelism between two episodes in the history of economic thought in order to suggest that the interaction between them can contribute to the research on Kaleckian growth and distribution models. First, a brief summary of the theoretical development from Steindl's stagnationist claims to the debate about demand regimes is offered. Then, a more detailed account is provided of the Latin American debate that began with Furtado's stagnationist claims and resulted in the formulation of models of social articulation and disarticulation. Finally, an analytical classification of Kaleckian and Latin American growth and distribution models is provided, indicating the way in which sectoral heterogeneity and demand composition can act as a plausible link between growth and distribution.
Keywords: E11; E20; O11; 330; Income distribution; Demand regimes; Sectoral heterogeneity; Demand composition; Distributive schedule